2008
DOI: 10.1007/s11882-008-0039-1
|View full text |Cite
|
Sign up to set email alerts
|

Occupational rhinosinusitis

Abstract: In contrast to most allergic rhinitis and nasal hyperresponsiveness, occupational rhinosinusitis offers a unique and effective measure-control of exposure-to reduce its medical impact on patients. Prospective data from adolescents introduced to the work environment show that working in high-risk environments results in a higher incidence of rhinitis compared with those not employed in such settings. Data also show that the highest incidence of occupational rhinosinusitis is found during the first months of exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…[95] Thisling et al , using the symptom-based definition of CRS, found that working in a blue collar job significantly increased the CRS prevalence in women but conversely, adjusted risk was significantly lower among male blue collar compared to male white collar workers. [79] Additionally, workplace exposure to “gases, fumes, dust, or smoke” increased the crude risk of CRS, although adjusted RR did not reach statistical significance.…”
Section: Outdoor and Indoor Air Qualitymentioning
confidence: 99%
“…[95] Thisling et al , using the symptom-based definition of CRS, found that working in a blue collar job significantly increased the CRS prevalence in women but conversely, adjusted risk was significantly lower among male blue collar compared to male white collar workers. [79] Additionally, workplace exposure to “gases, fumes, dust, or smoke” increased the crude risk of CRS, although adjusted RR did not reach statistical significance.…”
Section: Outdoor and Indoor Air Qualitymentioning
confidence: 99%
“…At present, it belongs to the most common occupational diseases of the airways, and it occurs 2-4 times more often than occupational asthma (OA) (2), though occupational asthma is more often diagnosed disease than OR. In the last years, there have been published several guidelines and review articles concerning OR (1,(3)(4)(5). However, the prevalence and incidence of occupational rhinitis has almost never been specifically researched (6).…”
Section: Introductionmentioning
confidence: 99%
“…Dados prospectivos de adolescentes apresentados ao ambiente de trabalho mostram que trabalhar em ambientes de alto risco resulta em maior incidência de rinite em comparação com aqueles não empregados em tais ambientes. Os dados também mostram que a maior incidência de RSO é encontrada durante os primeiros meses de exposição a substâncias irritantes e sensibilizantes, enfatizando a importância da prevenção precoce (Hellgren, 2008).…”
Section: Pbs-unclassified